Effect of Ultrasonic-Assisted Enzymolysis on Protein, Phenolic Content, and Antioxidant Activity of Chlorella sp. Crude Extract - Budiari, Setyani; Hamidatun, Hamidatun; Filailla, Euis; Artanti, Nina; Devi, Anastasia Fitria; Melanie, Hakiki; Maryati, Yati; Mulyani, Hani; Susilowati, Agustine; Aspiyanto, Aspiyanto (Squalen, Buletin Pascapanen dan Bioteknologi Kelautan dan Perikanan, 2023)
Chlorella sp. microalgae is a potential source of natural antioxidants and other bioactive compounds used in the food and pharmaceutical industries. Ultrasound pretreatments followed by enzymolysis are widely used to improve the functional properties of biological materials. This work aimed to investigate the effects of ultrasound pretreatments followed by bromelain hydrolysis on the proteins, phenolic content, and antioxidant activity of Chlorella sp. crude extract. The experimental design for the study involved two factors: ultrasound pretreatment time (0, 5, and 10 min) and bromelain hydrolysis time (0, 2, 4, and 6 hours). The protein was measured using Lowry assay while the total phenolic content was measured using a Folin–Ciocalteu assay. The highest protein content (7.09 ± 0.44 mg/mL) and phenolic concentrations (0.28 ± 0.01 ìg/mL) were obtained at 5 min ultrasound pretreatment and 6 hours enzymolysis. For antioxidant activity, 5 min ultrasound pretreatment followed by 4 hours of enzymolysis resulted in the highest DPPH (1,1-diphenyl-2-picrylhydrazyl radical) inhibitory activity (81.74%). Meanwhile, ultrasound pretreatment for 10 min followed by 6 hours of enzymolysis resulted in the highest ABTS (2,20 azinobis-(3-ethylbenzthiazoline-6-sulfonic acid) inhibitory activity (94.10%). This study showed that variation in ultrasound pretreatments followed by bromelain hydrolysis could be used to improve the protein content, phenolic content, and antioxidant activity of Chlorella sp. crude extract.